A Brief Neuropsychological Battery for Measuring Cognitive Functions Associated with Obesity. Issue 12 (25th October 2019) - Hovens, Iris B.; Dalenberg, Jelle R.; Small, Dana M.
Abstract : Objective: Although ample evidence links obesity to cognitive dysfunction, the trajectory of cognitive change, the underlying mechanisms, and the involvement of related factors, such as metabolic disease and diet, remain unclear. To support further investigations of BMI and cognition, this study aimed to create a concise test battery to be used in future trials. Methods: Twenty neurocognitive measures were regressed on BMI in the Human Connectome Project Healthy Young Adult S1200 data release by using linear mixed models and by adjusting for major confounders. Measures were then identified by using least absolute shrinkage and selection operator regression analysis to select tests most strongly associated with BMI. To guide further test selection, the explained variance for each variable was visualized in the final model. Results: BMI was negatively associated with seven neurocognitive measures. Variable selection yielded a model that included years of education and, in order of model weight, delay discounting, the relational task, the Penn Progressive Matrices test, the oral reading recognition test, the Variable Short Penn Line Orientation test, and the Penn Word Memory test. Conclusions: This research resulted in an approximate 40‐minute test battery for the BMI‐cognition relationship in young adults that can be used in trials investigating the interrelationship between obesity and cognitive performance.